Induced somatic and germinal reversion of the white-spotted-1 insertional mutant phenotype in Drosophila melanogaster. - Soriano, S.; Velazquez, A.; Marcos, R.; Cabre, O.; Xamena, N. (Mutagenesis, 1998)
The white-spotted-1 (Wsp1) mutant of Drosophila melanogaster is characterized by the presence of an 8.7 kb retrotransposon (B104) inserted in the regulatory region of the white locus. The frequency of reversion in both somatic tissue and the germline after exposure to three different alkylating agents has been analysed. To determine if germinal revertants were induced by precise excision of the insertional element we analysed several phenotypic revertants using PCR and Southern blot techniques. The results indicate that, under our experimental conditions, the mutagens used did not induce excision of B104 in the white gene. In addition, the revertant phenotypes obtained were due to the existence of second site modifiers acting on expression of white. Such modifiers map near the white locus and, at least in one case, may correspond to suppressor-of-white-spotted.